The impacts of NPD characteristics on innovation market performance and its survival: the mediating role of collaboration - Abdul Hamid, Norhadilah; Abd Rahman, Azmawani; Ahmad, Md. Fauzi; Ahmad, Ahmad Nur Aizat; Ngadiman, Yunos; Ismail, Siti Norziah (International Journal of Innovative Technology and Exploring Engineering, 2019)
While collaboration has been acknowledged as pertinent to the success of innovation product commercialization, the collaborative effort between the innovation recipient firm and the innovators remains limited.Besides,one of the central questions is how and under what condition the two parties are more likely to engage in a resilient collaborative effort, from the perspective of innovation recipient firms remain unclear.This new perspective requires an understanding of the relationships among new product Development (NPD) characteristics, collaboration, and product innovation market performance and survival within the context of technology transfer. In this paper, we employed transactional cost economic (TCE) theory to explain the relationships between NPD characteristics (innovation uncertainty and asset specificity) and collaboration,and the mediation effect of collaboration on the relationships between NPD and performance. Based on the response o 104 product innovation recipient firms, our findings suggest a positive relationship between NPD characteristics and, collaboration and market performance and innovation survival.This study revealed that consistent with TCE theory, NPD characteristics influence the pattern of ollaborationbetween the innovation recipient firms and the innovator, acted as an effort to reduce transactional risks. Our findings also concluded that collaboration mediates the relationship between NPD characteristics and market performance and innovation survival.